2019
DOI: 10.3748/wjg.v25.i47.6835
|View full text |Cite
|
Sign up to set email alerts
|

Trends in treatment and overall survival among patients with proximal esophageal cancer

Abstract: BACKGROUNDThe management of proximal esophageal cancer differs from that of tumors located in the mid and lower part of the esophagus due to the close vicinity of vital structures. Non-surgical treatment options like radiotherapy and definitive chemoradiation (CRT) have been implemented. The trends in (non-)surgical treatment and its impact on overall survival (OS) in patients with proximal esophageal cancer are unclear, related to its rare disease status. To optimize treatment strategies and counseling of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…In our cohort, only 15% of patients developing distant metastases received palliative chemotherapy. This corresponds to historical data in a large cohort of proximal EC [37], and reflects the limited high level evidence of palliative systemic therapy in metastatic esophageal SCC [38], as well as the frailty of this population.…”
Section: Discussionsupporting
confidence: 81%
“…In our cohort, only 15% of patients developing distant metastases received palliative chemotherapy. This corresponds to historical data in a large cohort of proximal EC [37], and reflects the limited high level evidence of palliative systemic therapy in metastatic esophageal SCC [38], as well as the frailty of this population.…”
Section: Discussionsupporting
confidence: 81%
“…When we compared our study results with those from a recently published retrospective study evaluating 500 Chinese CEC patients, we found a similar distribution of baseline characteristics between Western and Eastern countries ( 24 ). The proportion of patients receiving surgical resection in this unique setting was in accordance with a report from the Netherlands ( 25 ) that included 2,783 patients diagnosed with proximal esophageal cancers. The data revealed that surgical resection was performed in 17% of patients during 1989–1994 and in only 2% during 2010–2014.…”
Section: Discussionsupporting
confidence: 67%
“…First, by using weekly concurrent carboplatin and paclitaxel as the chemotherapy backbone rather than cisplatin and fluorouracil, treatment toxicity can be substantially reduced. [13][14][15] Second, by simultaneously integrating the boost dose, a biologically higher effective dose to the tumor can be delivered. Third, by using more modern radiation techniques, such as intensity-modulated techniques (IMRT, volumetric-modulated arc therapy), improved sparing of surrounding tissues can be achieved.…”
Section: Introductionmentioning
confidence: 99%